Cytotoxic potential of denture base and reline acrylic resins after immersion in disinfectant solutions - Masetti, Paula [UNESP]; Arbeláez, Maria Isabel Amaya [UNESP]; Pavarina, Ana Claudia [UNESP]; Sanitá, Paula Volpato [UNESP]; Jorge, Janaina Habib [UNESP] (Elsevier, 2018)
Statement of problem: The daily immersion of dentures in disinfectant solutions can cause the incorporation of toxic substances in the acrylic resins, and studies evaluating the cumulative effect of disinfectant solutions on cell culture are lacking. Purpose: The purpose of this in vitro study was to evaluate the cytotoxic potential of cell cultures of denture base and reline acrylic resins after immersion in disinfectant solutions. Material and methods: Disk-shaped specimens (14×1.2 mm) were obtained and divided into groups (n=9) according to the disinfectant solutions (distilled water [control], 2% chlorhexidine digluconate, 3.8% sodium perborate, 0.5% sodium hypochlorite, and apple vinegar) and to the storage period (0, 1, 3, and 6 months). Solutions were changed daily. After the different storage periods, specimens were immersed in culture medium for 24 hours, and extracts were obtained. Human keratinocytes were cultivated, and the cellular metabolism was evaluated by using Alamar Blue. Data were submitted to 3-way analysis of variance and Games-Howell post hoc tests (α=.05). Results: Both of the acrylic resins tested showed similar biocompatibility properties after immersion in different solutions (P=.400). Immersion in distilled water, 3.8% sodium perborate, and 0.5% sodium hypochlorite did not affect the cellular metabolism of the keratinocytes (P>.05), regardless of the immersion period and the type of acrylic resin (P>.05). Immersion in 2% chlorhexidine digluconate or apple vinegar resulted in high cytotoxicity over time, until the third month (P<.05), after which no changes were observed (P>.05). Conclusions: The type of acrylic resin (base or reline) had no significant effect on the viability of cells. Vinegar and chlorhexidine digluconate solutions increased in cytotoxic effect over time, and were strongly cytotoxic after 6 months of immersion. Sodium perborate and sodium hypochlorite were noncytotoxic in all periods of time tested.